Workload as Determinant of Teachers’ Job Satisfaction in Public Secondary Schools - Olaifa, Adeseko Sunday; Abisoye, Fausat Motunrayo; Adeoye, Moses Adeleke; Ajewole, Idowu Philip; Olaifa, Ebunlomo Oreoluwa (Universitas Pendidikan Ganesha, 2024)
It has been observed that several teachers are leaving the teaching profession not because of poor salaries but because of a lack of job satisfaction. This study aims to analyze workload as a determinant of teachers’ job satisfaction in public secondary schools in Oyo State, Nigeria. The descriptive survey research design was used. Three research questions were raised to guide the study. The study used a sample size determination to select 183 schools and 1,363 teachers. The research instrument used a self-designed questionnaire titled ‘Workload and Teachers’ Job Satisfaction Questionnaire was analyzed using frequency, counting, percentage, mean and standard deviation. The findings of the study provide valuable insights into the impact of workload on teachers' job satisfaction. The study found that as workload increases, job satisfaction decreases. This suggests that high levels of workload negatively affect teachers' overall satisfaction with their jobs. The results also revealed that teachers in public secondary schools in Oyo State are facing a heavy workload. It can be concluded that there is a significant correlation between workload and job satisfaction among teachers in public secondary schools in Oyo State. It was recommended that the school workload of the teachers in terms of working time and class size should be well maximized in other to improve the teachers’ job satisfaction.